Pengaruh Penambahan Abu Serbuk Kayu Jati terhadap Kuat Tekan dan Serapan Air pada Paving Block - Ruswanto, Taufik Adi; , Budi Setiawan, S.T., M.T (2017)
Paving blocks made up of a mixture of cement, water and fine aggregate. When cement and water mixed there will be a process of hydration of cement produce calcium silicate hydrate (CSH), heat and calcium hydroxide (Ca (OH) 2). Elements Ca (OH) 2 strongly alkaline so that the lower the compressive strength of paving blocks. The element can be reacted back with pozzolan to produce elements of CSH back. However, with a relatively expensive, arising out new innovations to treat waste that has elements in common with the pozzolan is silica such as waste sawdust. Teak wood powder waste mixed with burned for several hours. The resulting ash sifted using a sieve No. 200. The test object is printed using a press machine vibration with additional variations of gray teak wood powder 10%, 15%, 20%, and 25% and soaked for 28 days. Average compressive strength generated by the variation is 11.083 MPa, 9.917 MPa, 10,083 MPa and 8,250 MPa. With water absorption of 7.83%, 7.79%, 8.59% and 8.05%. Gray paving blocks with the addition of sawdust decreased compressive strength of normal paving block is 15.167 MPa. From these studies it is known that the maximum value in increments of 20% of the block paving including quality category D, used to park and use need to do further research for additional variations and other types of wood to get a paving block with better quality.